2022
DOI: 10.1097/aog.0000000000005016
|View full text |Cite
|
Sign up to set email alerts
|

No-Test Medication Abortion

Abstract: To summarize the effectiveness and safety outcomes of medication abortion performed without prior pelvic examination or ultrasonogram ("no-test medication abortion"). DATA SOURCES:We searched the MEDLINE, Scopus, Web of Science, Cochrane (including ClinicalTrials.gov), CINAHL, Global Index Medicus, and CAB Direct databases to identify relevant studies published before April 2022 using a peer-reviewed search strategy including terms such as "medication abortion" and "ultrasonography." We contacted experts in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…A multicenter retrospective cohort study reported similar effectiveness for no-test medication abortion whether medications were dispensed in-person (95.4%) or with telemedicine by mail (93.3%) 48 . These findings are also consistent with a systematic review of 21 studies of no-test medication abortion, including self-sourced, in-clinic, and telemedicine dispensing, with a cumulative efficacy of 96.4% completed abortions without surgical intervention 53 . The preponderance of evidence supports that medication abortion by telemedicine, with or without preabortion testing, is similarly effective to in-person care.…”
Section: Effectiveness Of Telemedicine Abortionsupporting
confidence: 72%
“…A multicenter retrospective cohort study reported similar effectiveness for no-test medication abortion whether medications were dispensed in-person (95.4%) or with telemedicine by mail (93.3%) 48 . These findings are also consistent with a systematic review of 21 studies of no-test medication abortion, including self-sourced, in-clinic, and telemedicine dispensing, with a cumulative efficacy of 96.4% completed abortions without surgical intervention 53 . The preponderance of evidence supports that medication abortion by telemedicine, with or without preabortion testing, is similarly effective to in-person care.…”
Section: Effectiveness Of Telemedicine Abortionsupporting
confidence: 72%
“…Complication rates were low as well, with 4.4% of patients requiring a uterine evacuation procedure and a 0.06% rate of ectopic pregnancy. 12…”
Section: Modes Of Deliverymentioning
confidence: 99%
“…Data from ‘no-touch’ abortion protocols – medication abortion given without a dating ultrasound – provides insight into the frequency of complications that may be expected after SMA. In a large systematic review including over 10 000 patient outcomes, Pearlman Shapiro et al [17 ▪▪ ] found the overall rate of surgical evacuation was 4.4% (95% CI 4.0–4.9), blood transfusion 0.5% (95% CI 0.3–0.6), and ectopic pregnancy 0.06% (95% CI 0.02–0.15) in those using no-touch protocols. Although the rate of ectopic pregnancy in this population was low, emergency physicians must be aware of this potential risk and maintain a high index of suspicion when an intrauterine pregnancy was not previously confirmed.…”
Section: Abortion Carementioning
confidence: 99%